2021
DOI: 10.1101/2021.07.22.21260760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of mouthwash sampling in SARS-CoV-2 diagnosis

Abstract: Background The current practice of COVID 19 diagnosis worldwide is the use of oro nasopharyngeal (ONP) swabs. Our study aim was to explore mouthwash (MW) as an alternative diagnostic method, in light of the disadvantages of ONP swabs. Methods Covid-19 outpatients molecular confirmed by ONP swab were repeatedly examined with ONP swab and MW with normal saline (0.9%). Other types of fluids were compared to normal saline. The Cq values obtained with each method were compared. Results Among 137 pairs of ONP swa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…After screening the titles and abstracts of the remaining articles, 45 full texts were screened (figure 1). On the basis of our selection criteria, 27 of those studies were excluded and 18 studies [28,29,35,36,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] met our inclusion criteria (table 1). One study examined two study populations, of suspected infection and of confirmed cases, which were analysed separately [59].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening the titles and abstracts of the remaining articles, 45 full texts were screened (figure 1). On the basis of our selection criteria, 27 of those studies were excluded and 18 studies [28,29,35,36,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] met our inclusion criteria (table 1). One study examined two study populations, of suspected infection and of confirmed cases, which were analysed separately [59].…”
Section: Resultsmentioning
confidence: 99%
“…Of these 19 study populations, seven assessed the diagnostic performance of gargle in populations with suspected infection [28,49,50,54,55,57,59], and 12 assessed the use of gargle for monitoring viral shedding in populations already confirmed to have SARS-CoV-2 infections, either as hospital inpatients or after being discharged (table 1) [29, 35, 36, 46-48, 51-53, 56, 58, 59]. Regarding the study location, there were five studies from Canada [28,47,50,52,57], six from Germany [36,48,49,51,54,56] and with the rest (seven) from Finland [29], Turkey [55], China [46], Korea [58], Indonesia [59], Israel [53] and India [35]. These studies spanned from 23 March 2020 to 19 July 2021, covering the period of different prevailing SARS-CoV-2 variants, from the ancestral strain, alpha variant, to its delta variant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the method was rapidely available and independent of the most limited resource in the early phase of the pandemics besides PCR reagents, namely swabs. Meanwhile several studies have been published that also made use of throat washes or saliva, although these studies suggested to the community that this sampling procedure was entirely novel [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“… 23 Previous studies indicated that sample collection can be feasibly improved to increase the sensitivity of saliva for PCR by using a saliva swab and supervised self-saliva collection, 26 self-collected deep throat saliva, 24 , 25 , 27 or rinse–gargle saliva. 28 , 29 Additional improvements of the LAMP method include the selection of alternative gene targets, such as the N gene or simultaneously use of multiple genes as targets such as E, N, and Orf, 30 33 as well as optimized sample processing to minimize interference from the specimen pH, especially for FS, with the colorimetric method. Other enhancements could include the use of a thermal cycle machine, a digital or fluorescence reader for amplification detection, and insulated containers to stabilize the incubation temperature for the LAMP reaction.…”
Section: Discussionmentioning
confidence: 99%